STUDI EVALUASI PENGARUH VARIASI MUTU BETON TERHADAP KEKUATAN STRUKTUR BETON NORMAL MENGGUNAKAN METODE NON-DESTRUCTIVE TEST DAN DESTRUCTIVE TEST - Bagas Bhanu Aribawa; Indradi Wijatmiko; Roland Martin Simatupang (Rekayasa Sipil, 2019)
To make the examination of the strength of existing building structures easier, can be done by using the Non-Destructive Test (NDT) methods, but the results obtained are not as accurate as using the Destructive Test (DT) method. It is therefore a study related to the combination of NDT and DT methods to obtain better accuracy of the results. The research uses PUNDIT PL-200, Silver Schmidt Hammer, Compression Testing Machine with 3 concrete quality types of 12,5 MPa, 18,75 MPa, and 25 MPa. Overall results, UPV and the actual compressive strength have a close and mutually affecting relationship between the variables evidenced by the R2 value of 0,7458. In addition, with the presence of combinations of several variables testing methods of DT and NDT, it can produce a level of accuracy from a compressive strength estimate value.